Quiste epidermoide: reporte de once casos y revisión de literatura - Francisco Levi Duque-Serna; Gloria Jeanethe Alvarez-Gómez; José Nayib Radi-Londoño (Universidad de Antioquia, 2001)
The epidermoid cyst is a very rare pathology of the facial area occurring in head and neck in only 6.9% of the cases and whose origin is still controversial. Clinically it is characterized by having a slow growth and it may cause multiple facial alterations. We are presenting 11 epidermoid cyst cases in the maxillofacial region. The age range is between 2 months and 62 years of age and the sizes vary between 0.6 cms and 9.0 cms. These epidermoid cysts were producing deglutition and phonation alterations along with tongue displacement. The diagnostic tools of choice are the magnetic resonance imaging and the computerized axial tomography using contrast media since this is a soft tissue lesion. A needle biopsy of the mass helps to clarify the diagnosis but, once the cyst is enucleated, the appropriate anatomopathologic study should be done to obtain the final diagnosis.